Risk of disability due to car crashes: a review of the literature and methodological issues. - Ameratunga, SN; Norton, R; Bennett, D; Jackson, RT (2004)
With improving rates of survival following road traffic injuries in many countries, healthy years of life lost due to crashes increasingly reflect the prevalence of disabling sequelae. This review examines the epidemiological evidence regarding the risk of disability due to car crashes, published between 1980 and 2002. Studies of sequelae limited to specific domains (e.g. head injury, whiplash, psychiatric morbidity) were excluded. Of the 19 studies meeting the criteria for review, most focused on the prevalence of disability following crashes but not the association between them. Prevalence estimates of post-crash disability varied from 2 to 87%. The potential sources of heterogeneity included differences in study settings and period, duration of follow-up, and definitions of exposure and outcome. Methodological problems that compounded the difficulties in interpretation and generalisability of study findings included selection biases and use of non-representative samples, idiosyncratic outcome measures, inadequate adjustment for confounding, and the prevailing medico-legal or compensation context. The findings highlight the need for well-designed population-based epidemiological studies using validated outcome measures and appropriate comparison groups to determine the independent risk of disability due to car crashes. The review also revealed a critical need for data from low- and middle-income countries, the setting for over 90% of the estimated global burden of road traffic injury.